Principles and practice of clinical research - Gallin, John I.; Ognibene, Frederick P. (Elsevier /Academic Press, 2012)
This expanded third edition provides an introduction to the conduct of clinical research as well as more comprehensive and expansive content about the infrastructure necessary for a successful clinical research organization or enterprise. With authors who are experts in clinical research in both the public and private sectors, this publication provides essential information to clinical investigators who wish to develop and conduct well designed patient-based research protocols that comply with rigorous study design, ethical, and regulatory requirements.